Development and evaluation of an enzyme-linked immunosorbent assay based on recombinant TgSRS2 for serodiagnosis of Toxoplasma gondii infection in cats - GAO, Yang; GUO, Huanping; MOUMOUNI, Paul Franck Adjou; LIU, Mingming; LI, Jixu; EFSTRATIOU, Artemis; GALON, Eloiza May; YBANEZ, Rochelle Haidee; MASATANI, Tatsunori; SOMA, Takehisa; XUAN, Xuenan (Journal of Veterinary Medical Science, 2020)
An enzyme-linked immunosorbent assay (ELISA) based on recombinant SAG1-related sequence 2 of Toxoplasma gondii (rTgSRS2) was developed to detect toxoplasmosis in cats. The specificity and sensitivity of rTgSRS2 ELISA were confirmed using a series of serum samples from T. gondii-experimentally infected mice. A total of 76 field samples from cats were examined by the developed ELISA. The rTgSRS2 ELISA showed a good diagnostic performance characterized by high concordance (88.16) and kappa value (0.76) with latex agglutination test (LAT). The sensitivity and specificity of the test were 92.68% and 82.86%, respectively. These results suggest that the ELISA based on rTgSRS2 could be a useful tool for serodiagnosis of T. gondii infection in cats.